The Correlation Between Reading Attitude and Reading Comprehension Achievement - Renny Nur Ferlyanti; Shynta Amalia; Hariana Amalia (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
This research aimed to investigate the correlation between reading attitude and reading comprehension achievement among eleventh-grade students at MAN 1 Lahat. A correlational research method was employed to assess the relationship between these two variables. The study's population comprised nine classes of eleventh-grade students, from which a sample of 98 students was selected through convenience sampling. Data collection involved administering a reading attitude questionnaire designed to measure students' perceptions and feelings toward reading and a reading comprehension test to evaluate their comprehension skills. The correlation between the collected data was analyzed using SPSS 25 software. The findings revealed a correlation coefficient (r) of 0.011, significantly lower than the critical value of the r-table, set at 0.913. These results indicate a weak and statistically insignificant correlation between reading attitude and reading comprehension achievement among the eleventh-grade students at MAN 1 Lahat. Thus, it can be concluded that while there may be some relationship between these variables, the strength of this correlation is not sufficient to be considered meaningful within this specific educational context. Further research could be beneficial to explore additional variables that may significantly impact students’ reading achievements. Understanding these dynamics can provide educators with valuable insights into improving reading instruction and fostering better student comprehension skills.